Secondary Xylem Anatomy of Root and Stem of Alstonia scholais, Bischhiofia javanica and Trewia nudiflora: The Characteristic Plant Species of Manu Fresh Water Swamp, Rishikesh, Dehradun (India) - Pande, P. K.; Ghyldiyal, J. C.; Gautam, Pallavi (Indian Forester, 2013)
The paper presents a comparative account of root and shoot secondary xylem anatomy of Alostonia scholaris R. Br (Family: Apocynaceae), Bischofia javanica Blume and Trewia nudiflora Linn. (Family: Euphorbiaceae) of Manu swamp, Rishikesh, Dehradun (India). Fiber dimensions and vessel element diameter of secondary xylem of shoot were higher than that of roots. Moreover, vessel and ray frequencies were higher in roots whereas the size of inter vessel pits was more in shoots of all the three species. Further, parenchyma is diffuse in aggregate, scanty paratracheal and vesicentric in roots and scanty paratracheal in shoots of A. scholoaris; diffuse, in aggregate and scanty paratracheal in shoot while only diffuse in root of B. javanica, and diffuse, in aggregate and scanty paratracheal in shoot while scanty paratracheal in root of T. nudiflora. Other anatomical features of root and shoot anatomy of secondary xylem are more or less similar in A. scholaris, B. javanica and T. nudiflora.